Microbiological analysis of bacterial sealing of internal conical implants with different taper angles - Laura Firmo de CARVALHO; Alexandre Marcelo de CARVALHO; Bruno Salles SOTTO-MAIOR; Carlos Eduardo FRANCISCHONE; Elizabeth Ferreira MARTINEZ; André Luiz DIAS; Liliane Pacheco de CARVALHO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The present study evaluated the effect of the taper angle of different internal conical connection implants and cyclic loading on the implant-abutment bacterial seal. A total of 96 implant-abutment sets were divided into eight groups. Four groups of different taper degrees with cyclic mechanical loading of 500,000 cycles per sample, with a 120-N load at 2 Hz before analysis [16DC (16-degree, cycled), 11.5DC (11.5-degree, cycled), 3DC (3- degree, cycled) and 4DC (4- degree, cycled)] were compared to four control groups without cyclic loading [16D (16-degree), 11.5D (11.5-degree), 3D (3-degree), and 4D (4-degree)]. Microbiological analysis was performed by immersing all samples in a suspension containing Escherichia coli and incubating them at 37°C. After 14 days, the presence of bacterial seals was evaluated. Fisher-Freeman-Halton exact tests and binomial tests were performed (5% significance level). The groups showed significant differences in bacterial seal, and mechanical load cycling improved the bacterial seal in the 3DC group. In all other groups, no significant differences in bacterial seal were found between cycled and uncycled samples. To conclude, the internal conical connection with a 3-degree taper angle showed better results than the other connection with different angles when subjected to load cycling. However, none of the angles tested were fully effective in sealing the implant-abutment interface.